(untitled) (Baltic Journal of Sport and Health Sciences, 2020)
Background. Both fasting and ageing processes lead to muscle wasting. We studied the effect of single 48 h fasting on soleus skeletal muscle mass and force in young and old mice. Methods. The study involved 18 young and 13 old mice. Body and soleus (SOL) muscle mass were measured followed by assessment of peak and specific SOL force under ex vivo conditions. SOL muscle half-relaxation time and 20 Hz to 100 Hz force ratio were also measured. Results. After fasting, weight loss was greater (p < .05) in young mice compared to old mice (17.0 ± 2.6 versus 12.0 ± 1.7%, respectively). Fasted young, but not old mice showed reduction (p < .05) in SOL mass compared to the control values. On the other hand, specific SOL force was reduced (p < .05) only in old mice, while 20 Hz to 100 Hz force ratio decreased (p < .05) only in young mice after fasting. Conclusions. Our results showed that 48 h fasting caused lower SOL muscle peak and specific force in old but not young mice. Keywords: starvation, peak force, specific force, ageing.